Skin transcriptomics of invasive Coqui frogs: stress responses, parasite signatures, and antimicrobial peptides. - Randy Ortiz; Leeann C Dabydeen; Carolyn Kosinski; Priyanka Gera; Juan D Carvajal-Castro; Victoria Akilov; Hunter J Howell; Emily Powell; Juan C Santos (PLoS ONE)
Resilience in amphibians lies in their ecological adaptability, driven by their genetic makeup. Eleutherodactylus coqui, native to Puerto Rico (PR) and a beloved symbol there, is among the most successful invasive amphibians. This species is extensively studied in terms of its biology and genetics, including being the first Eleutherodactylus with a draft genome. Its potential to spread to new habitats and rapid breeding are notable. Transcriptome analyses of E. coqui are limited but provide insights into their invasiveness and differential gene expression. We compared the skin transcriptomes of E. coqui from PR (native) to those from an area under citric acid treatment in Los Angeles, California (invasive) population. Our results show differences in stress response gene signatures between both populations. In the native population, we hypothesize these responses are due to immunity against diverse parasites, potentially helping control their native populations in PR. Additionally, these coquis expressed several antimicrobial peptides, which were previously reported to be absent in coquis. These peptides may play a role in the invasiveness of the common coqui and its tolerance to urban and degraded habitats. We also provide novel draft transcriptomes of close relatives of E. coqui: Eleutherodactylus planirostris, Eleutherodactylus johnstonei, Eleutherodactylus cochranae, and Pristimantis unistrigatus.